Age, Time, and Decision Making: From Processing Speed to Global Time Horizons - Löckenhoff, Corinna E. (2011)
Time and time perceptions are integral to decision making because any meaningful choice is embedded in a temporal context and requires the evaluation of future preferences and outcomes. The present review examines the influence of chronological age on time perceptions and horizons and discusses implications for decision making across the life span. Time influences and interacts with decision making in multiple ways. Specifically, this review examines the following topic areas: (1) processing speed and decision time, (2) internal clocks and time estimation, (3) mental representations of future time and intertemporal choice, and (4) global time horizons. For each aspect, patterns of age differences and implications for decision strategies and quality are discussed. The conclusion proposes frameworks to integrate different lines of research and identifies promising avenues for future inquiry.